Meningkatkan Kemampuan Menari Tidi Lo O’ayabu Melalui Model Pembelajaran Project Based Learning Pada Murid Kelas IV MIM Unggulan Kota Gorontalo - Delawati Gintulangi; Mimy Astuty Pulukadang; Nurainun; La Ode Karlan; iwy Triyanty Pulukadang (DE FACTO : Journal Of International Multidisciplinary Science, 2026)
The ability of fourth-grade students at MIM Unggulan Kota Gorontalo to perform the Tidi Lo O’ayabu dance was still relatively low. This study aimed to improve students’ dancing skills through the implementation of the Project Based Learning (PjBL) model. The method used was Classroom Action Research (CAR), conducted in two cycles involving 15 female students. Data were collected through observation, tests, and documentation, and then analyzed using descriptive quantitative analysis based on the aspects of wiraga, wirama, and wirasa. The results showed an improvement in dancing skills from 7% during the initial observation to 27% and 53% in Cycle I, and further increased to 67% and 87% in Cycle II. These achievements exceeded the predetermined success indicator of 80%. In addition, teacher and student activities improved from the sufficient category to the good category. Therefore, PjBL was proven effective in improving students’ Tidi Lo O’ayabu dancing skills systematically and consistently.